Efficacy of quercetin flavonoid in recovering the postbleaching bond strength of orthodontic brackets: A preliminary study - Mana Shamsedin; Valiollah Arash; Masoud Babaei Jahromi; Ali Akbar Moghadamnia; Manouchehr Rahmati Kamel; Fariba Ezoji; Ali bijani; Samira Kavoli; Tania Ghasemi; Gholamhossein Ramezani (Wolters Kluwer Medknow Publications, 2017)
Objectives: To evaluate comparatively the effect of quercetin on postbleaching shear bond strength (SBS) and adhesive remnant index (ARI). Materials and Methods: Intact maxillary premolars were divided randomly into 12 groups of 10 each: (1) bonding the bracket immediately after bleaching, (2) bonding 1 week after bleaching, (3-8) application of three experimental concentrations of quercetin (0.1%, 0.5%, and 1%) at two time durations (5 and 10 min), (9-10) application of the solvent of quercetin at two time periods (5 and 10 min), (11) application of 10% sodium ascorbate for 10 min, and (12) bonding the brackets on nonbleached teeth. Bleaching was performed using 15% carbamide peroxide gel for 5 days (6 h daily). After incubation and thermocycling, the SBS of brackets was measured. The ARI too was recorded at ×20. The data were analyzed statistically (α =0.05). Results : Bleaching reduced the SBS below 10 Megapascal (MPa) level (P < 0.05) while all the postbleaching treatments (except the application of the solvent of quercetin) recovered the SBS back to values greater than 10 MPa (P < 0.05) and also back to nonbleached SBS levels (P > 0.01). All eight postbleaching treatments had rather similar efficacies (P = 0.1396). The concentration of quercetin (beta = 0.259, P = 0.042) but not its duration (beta = 0.213, P = 0.093) significantly improved its efficacy. Conclusion: Bleaching can weaken the bond strength of orthodontic brackets below acceptable levels. The application of quercetin or Vitamin C or delaying the bracket bonding improved the postbleaching SBS.